2010
DOI: 10.1177/0022167810382454
|View full text |Cite
|
Sign up to set email alerts
|

Parent’s Conception and Experience of Calling in Child Rearing

Abstract: The concept of "calling" has evolved from a religiously oriented description of occupation to an integrated, broad, and multidimensional construct that is associated with optimal vocational outcomes, personal fulfillment and meaning, and contribution to the "greater good." This article investigates the relevance of calling in the parental domain and explores the experience of calling in child rearing. Using interpretative phenomenological analysis, 11 qualitative, semistructured interviews were conducted with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(43 citation statements)
references
References 31 publications
0
43
0
Order By: Relevance
“…Participants in previous research indicated discomfort with religious connotations implied by the notion of calling (Coulson et al, 2010). Some parents were also uncomfortable with their own conception of calling as something that takes away autonomy and freedom to choose one's life path.…”
Section: Item Selectionmentioning
confidence: 96%
See 4 more Smart Citations
“…Participants in previous research indicated discomfort with religious connotations implied by the notion of calling (Coulson et al, 2010). Some parents were also uncomfortable with their own conception of calling as something that takes away autonomy and freedom to choose one's life path.…”
Section: Item Selectionmentioning
confidence: 96%
“…Baumeister (1991) indicated a noble and respected calling is that of 'housewife and mother' (p. 126). Furthermore, a small amount of qualitative work (Coulson, Oades, & Stoyles, 2010;Oates et al, 2005;Sellers, Thomas, Batts, & Ostman, 2005) has investigated calling in childrearing, demonstrating its relevance in this context. To date there has been no evidence of quantitative investigations into the examination of calling in childrearing.…”
Section: Calling In Childrearingmentioning
confidence: 99%
See 3 more Smart Citations